A Water‐/Fireproof Flexible Lithium–Oxygen Battery Achieved by Synergy of Novel Architecture and Multifunctional Separator. Issue 1 (27th November 2017) - Yin, Yan‐Bin; Yang, Xiao‐Yang; Chang, Zhi‐Wen; Zhu, Yun‐Hai; Liu, Tong; Yan, Jun‐Min; Jiang, Qing
Abstract: To meet the increasing demands for portable and flexible devices in a rapidly developing society, it is urgently required to develop highly safe and flexible electrochemical energy‐storage systems. Flexible lithium–oxygen batteries with high theoretical specific energy density are promising candidates; however, the conventional half‐open structure design prevents it from working properly under water or fire conditions. Herein, as a proof‐of‐concept experiment, a highly safe flexible lithium–oxygen battery achieved by the synergy of a vital multifunctional structure design and a unique composite separator is proposed and fabricated. The structure can effectively prevent the invasion of water from the environment and combustion, which is further significantly consolidated with the help of a polyimide and poly(vinylidene fluoride‐ co ‐hexafluoropropylene) composite separator, which holds good water resistance, thermal stability, and ionic conductivity. Unexpectedly, the obtained lithium–oxygen battery exhibits superior flexibility, water resistance, thermal resistance, and cycling stability (up to 218 cycles; at a high current of 1 mA and capacity of 4 mA h). This novel water/fireproof, flexible lithium–oxygen battery is a promising candidate to power underwater flexible electronics. Abstract : A highly safe flexible lithium–oxygen (SFLO) battery is designed and fabricated to endow the possibility to power versatile portable and flexible devices. Thanks to an innovative assembly method, the structure of the SFLO battery possesses good flexibility, excellent water‐ and fire‐resistance, and superior electrochemical performances.